Association between facial expression and PTSD symptoms among young children exposed to the Great East Japan Earthquake: a pilot study - Fujiwara, Takeo; Mizuki, Rie; Miki, Takahiro; Chemtob, Claude (Frontiers in Psychology, 2015)
“Emotional numbing” is a symptom of post-traumatic stress disorder (PTSD) characterized by a loss of interest in usually enjoyable activities, feeling detached from others, and an inability to express a full range of emotions. Emotional numbing is usually assessed through self-report, and is particularly difficult to ascertain among young children. We conducted a pilot study to explore the use of facial expression ratings in response to a comedy video clip, and to assess emotional reactivity among preschool children directly exposed to the Great East Japan Earthquake. This study included 23 child participants. Child PTSD symptoms were measured using a modified version of the Parent’s Report of the Child’s Reaction to Stress scale. Children were filmed while watching a 2-minute video compilation of natural scenes (‘baseline video’) followed by a 2-minute video clip from a television comedy (‘comedy video’). Children’s facial expressions were processed using Noldus FaceReader software, which implements the Facial Action Coding System (FACS). We investigated the association between PTSD symptom scores and facial emotion reactivity using linear regression analysis. Children with higher PTSD symptom scores showed a significantly greater proportion of neutral facial expressions, controlling for sex, age and baseline facial expression (p < .05). This pilot study suggests that facial emotion reactivity could provide an index against which emotional numbing could be measured in young children, using facial expression recognition software. This pilot study adds to the emerging literature on using experimental psychopathology methods to characterize children’s reactions to disasters.